Tobacco Cessation Counseling and Medications Provided by Physicians to Tobacco Users During Primary Care Visits - Karen W. Geletko; Katelyn Graves; Hanna Lateef; Jeffrey Harman (SAGE Publishing, 2022)
Introduction: The established guidelines for treating tobacco use and dependency is brief provider intervention to assist those willing to quit by providing access to medication and/or behavioral counseling. The purpose of the study is to determine the extent of cessation treatment offered by providers during primary care visits by patients who are current tobacco users, and to examine associations between patient factors and treatment received. Methods: Using data from the 2015 to 2018 National Ambulatory Medical Care Survey (NAMCS), we examined tobacco cessation counseling and medications from 4590 visits by patients with current tobacco use. Separate multivariate logistic regressions were used to assess whether the odds of receiving tobacco cessation treatment varied by age, gender, race/ethnicity, and payment source. Results: Of visits by current tobacco users, 18.4% included cessation counseling, 5.5% included cessation medication, and 22.1% included at least 1 type of treatment. Visits by patients with Medicare had 44% greater odds of including counseling (CI = 1%-205%) and treatment (OR = 1.44; 95% CI = 1.01-2.06). Visits classified as "other payment type" had 73% greater odds of including counseling (OR = 1.73; 95% CI = 1.05-2.84). Visits by women had 86% greater odds of including medication (CI = 17%-294%). Conclusions: Tobacco cessation treatment is underutilized by providers during primary care visits. Further research is necessary to understand and address barriers to providing routine cessation assistance.